1972
DOI: 10.1071/ar9720779
|View full text |Cite
|
Sign up to set email alerts
|

Germination of annual ryegrass seeds (Lolium rigidum Gaud.) as influenced by temperature, light, storage environment, and age

Abstract: Germination of Lolium rigidum seeds, in the light (12 hr day length) and in the dark, at constant temperatures of 12, 18, and 24°C and an alternating temperature of 24/12" (12112 hr), was studied in freshly harvested seeds and in seeds stored for 18 weeks. In freshly harvested seeds the highest germinability (80%) was recorded at 12' in either light or dark and at 24/12' in the light. After 18 weeks' storage, a germinability of between 95 and 100% was observed at 12" and 24/12" in the dark and at 24' and 24/12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

1986
1986
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…In Australia, L. rigidum predominantly occurs in the southern Mediterranean regions with their wet winters and dry summers. As a result, most of the research work related to L. rigidum has been done in these regions e.g burial and longevity studies (Gramshaw 1972;Gramshaw and Stern 1977) and herbicide resistance studies (Preston et al 1999). A survey of the lower Liverpool Plains in northern New South Wales in 2001 showed that glyphosate resistant L. rigidum was present on at least 10 farms, with infestations varying from small patches of plants to being widespread across the whole farm (Storrie and Cook 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Australia, L. rigidum predominantly occurs in the southern Mediterranean regions with their wet winters and dry summers. As a result, most of the research work related to L. rigidum has been done in these regions e.g burial and longevity studies (Gramshaw 1972;Gramshaw and Stern 1977) and herbicide resistance studies (Preston et al 1999). A survey of the lower Liverpool Plains in northern New South Wales in 2001 showed that glyphosate resistant L. rigidum was present on at least 10 farms, with infestations varying from small patches of plants to being widespread across the whole farm (Storrie and Cook 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Or will a heavy clay soil from the northern region speed or slow seedbank decline? Lolium rigidum is thought to have a short dormancy cycle (Gramshaw 1972;Gramshaw and Stern 1977) but the factors which directly or indirectly affect dormancy, viability, germination and emergence of L. rigidum require further research.…”
Section: Introductionmentioning
confidence: 99%
“…Seeds of different crops manifest three distinctive germination requirements regarding light: seeds that require light for germination, those that require the absence of light, and seeds that are indifferent to light (Aiken and Springer, 1995;Cole et al, 1974;Gramshaw, 1972). Seeds of different crops manifest three distinctive germination requirements regarding light: seeds that require light for germination, those that require the absence of light, and seeds that are indifferent to light (Aiken and Springer, 1995;Cole et al, 1974;Gramshaw, 1972).…”
mentioning
confidence: 99%
“…The effect of light on seed germination has three main components: quantity, duration, and quality. Seeds of different crops manifest three distinctive germination requirements regarding light: seeds that require light for germination, those that require the absence of light, and seeds that are indifferent to light (Aiken and Springer, 1995;Cole et al, 1974;Gramshaw, 1972).…”
mentioning
confidence: 99%
“…This study revealed both similarities and differences in comparison with previous studies of rigid ryegrass. The first similarity is that after-ripening during summer widens the temperature range for the germination of Italian ryegrass seeds, which also has been observed for rigid ryegrass (Gramshaw 1972). The Italian ryegrass seeds tested soon after harvest generally exhibit a high level of postharvest dormancy (Hides et al 1993).…”
Section: Discussionmentioning
confidence: 71%